Time, Care, and Solidarity in Decolonial, Anti-Racist, Anti-Ableist Undergraduate Program Building - Ki, Patricia Hoi Ling; da Silveira Gorman, Rachel; Vorstermans, Jessica; Berthelot-Raffard, Agnès; Hillier, Sean; Delaviz, Yasaman (Intersectionalities, 2024)
This article reflects on the development process of a new undergraduate program, Racialized Health and Disability Justice (RHDJ), at the Critical Disability Studies program, York University from the perspective of the core program development team. The RHDJ program aims to centre the contributions and scholarship of Black, Indigenous, racialized, disabled, and Mad peoples, in response to mounting evidence demonstrating the ongoing marginalization and neglect of these groups in terms of their health and well-being across the Canadian state, and their exclusion from participation, recognition, knowledge production, and leadership within the colonial structures of academia. We reflect on how graduate students and faculty were involved in working toward the program’s central aim of teaching and enacting racial and disability justice. We ask, what difference does it make in our program development process to begin from a disability justice ethos, in our negotiations within a structure that the program resists at the same time as it relies on it for its existence? Since the program aims toward the transformation of care for communities who have been marginalized, we also consider if theories of care ethics can inform our process in implementing disability justice principles as we navigate institutional barriers, organization of labour, and collaboration. By sharing our process and reflections, we hope other collectives with similar disability justice goals may consider and build upon our experiences, in the service of building different tools for a different, more livable future.